A young church in mission or maintenance mode?: A case study of the Bantu Presbyterian Church of South Africa (1923-1999) - Duncan, Graham Alexander (Missionalia, 2019)
The Bantu Presbyterian Church of South Africa (BPCSA) was the first autonomous South African church to be established in 1923 as the result of the work of the mission of a Church of European origin (CEO). It had taken one hundred years after the first missionaries of the Glasgow Missionary Society and subsequently the Free Church of Scotland and the United Presbyterian Church of Scotland, which united in 1900 to form the United Free Church of Scotland, had arrived in the Eastern Cape to form an autonomous church. It would continue to pursue its missionary strategy for the next seventy-six years until it united with the Presbyterian Church of Southern Africa in 1999 to form the Uniting Presbyterian Church of Southern Africa. The aim of this article is to explore the extent to which it remained true to the mission of its founders and God’s mission as it became institutionalised. The ecumenical aspect of mission has already been dealt with and will not be considered here. This particular article will concentrate on internal church policies and activities including the role of missionaries, evangelists and church associations, theological education and socio-political issues. This is predominantly an exercise in primary archival research.